Direct enantioselective Bronsted acid catalyzed N-acyliminium cyclization cascades of tryptamines and ketoacids. - Holloway, C; Muratore, M; Storer, R; Dixon, D (2010)
A direct enantio- and diastereoselective N-acyliminium cyclization cascade through chiral phosphoric acid catalyzed condensation of tryptamines with γ- and δ-ketoacid derivatives to provide architecturally complex heterocycles has been developed. The reaction is technically simple to perform, atom-efficient, and broad in scope. Employing 10 mol % of (R)-BINOL derived chiral phosphoric acids in refluxing toluene allowed the polycyclic product materials to be generated in good yields (53-99%) and moderate to high enantioselectivities (68-98% ee).